Recent Progress in Essential Functions of Soft Electronic Skin. (20th July 2021) - Chen, Jianwen; Zhu, Yutian; Chang, Xiaohua; Pan, Duo; Song, Gang; Guo, Zhanhu; Naik, Nithesh
Abstract: Inspired by the human skin, electronic skins (e‐skins) composed of various flexible sensors, such as strain sensor, pressure sensor, shear force sensor, temperature sensor, and humility sensor, and delicate circuits, are emerged to mimic the sensing functions of human skins. In this review, the strategies to realize the versatile functionalities of natural skin‐like e‐skins, including strain‐, pressure‐, shear force‐, temperature‐ and humility‐sensing abilities, as well as self‐healing ability and other functions are summarized. Some representative examples of high‐performance e‐skins and their applications are outlined and discussed. Finally, the outlook of the future of e‐skins is presented. Abstract : Electronic skin is a type of soft electric device that possesses various sensing capabilities like the human skin. In this review, the strategies to realize the versatile functionalities of e‐skin, including strain‐, pressure‐, shear force‐, temperature‐ and humility‐sensing abilities, as well as self‐healing ability and other functions are summarized.